Regional Cultural Understanding in Teacher Education in Latvia, Lithuania, Norway: Comparative Case Analysis - Siliņa-Jasjukeviča, Gunta; Briška, Ilze; Juškevičienė, Agnė (Acta Paedagogica Vilnensia, 2019)
The unique cultural space of each country is comprised of the cultural diversity of its regions with the cultural heritage hidden in the outskirts and border areas of the country. The regional traditions make up an important source of value and knowledge for ensuring cultural sustainability. In teacher education this problem can be treated either in a transmissive or transformative way. It can be seen as performing particular rituals and respecting norms, or cultural values that are personally experienced and highly evaluated, as one’s internally motivated involvement in exploration, cultivation, cooperation and creativity in own community without losing the national and global context. The aim of the study is to investigate the tendencies in teacher education for promoting primary school students’ regional cultural understanding in teaching practice. To pursue the set aim, the concept of regional cultural understanding (RCU) was analysed, the ways of introducing regional cultural understanding in teacher education curriculum including the factors facilitating or hindering the development of regional cultural understanding in teacher education were identified. The comparative case analysis of good practice examples in three countries was carried out to show regularities, differences and similarities of possible pedagogical approaches. Methods: content analysis of educational documents and semi-structured interviews with teacher educators. Sample: teacher education institutions in three countries: Latvia, Lithuania and Norway. Results: structured suggestions for content of the studies and pedagogical approaches for development of preservice teachers’ readiness to realize regional cultural understanding in their teaching practice.